Rope Worm: Newly Discovered Parasite in Kuwait - Sher , Ali (Perspective of Recent Advances in Medical Research Vol. 1, 2022)
Rope worms are anaerobic creatures that were found in 2009 while the colon was being cleansed with coffee or cleansing enemas. They are parasitic worms, according to some scientists, while according to others, they are simply an accumulation of intestinal mucus and other debris. The intestinal parasites are twisted rope-like fibres that are metres long and connected to the intestinal wall. Rope worms have been discovered in the stools of thousands of people worldwide. The rope worms generate a slimy, sticky substance with a characteristic odor, twist like a corkscrew, and may obstruct the intestine. Based on their morphology, rope worms can be classified into five different stages. Additionally, it may cause gas, bloating, indigestion, constipation, and abdominal pain. In the area clinic, people have had multiple treatments with anthelminthic medications, but their symptoms have not improved. Without milk or water rectal enemas, the patients are unable to pass their stools.